Embrace your size : my own body positivity - Hara (Mangaka) (Yen Press, 2022)
What do you do when your body doesn't match the ideal shape as dictated by society? What do you wear when sweats seem to be the only clothes that fit you? How do you deal with the constant, overwhelming waves of criticism about your appearance from yourself and others? A love letter to anyone striving to embrace their size, this wonderfully illustrated, uplifting comic essay by a plus-size author chronicles her own journey with body positivity, what inspired her to change her mindset, and how she learned to love herself as she is.